2018
DOI: 10.1108/imefm-02-2017-0044
|View full text |Cite
|
Sign up to set email alerts
|

Earnings announcements, stock price reaction and market efficiency – the case of Saudi Arabia

Abstract: Purpose-This study aims to find the response by stock market against the announcements of quarterly earnings is empirically tested by exploiting event study methodology. Efficient market hypothesis (EMH) on Saudi stock exchange is also tried on. Design/methodology/approach-The market model is applied to help gauge the expected returns and to illustrate abnormal returns around the event date. Findings-The results established that Saudi Stock Market does not bear semi-strong form of EMH. How efficient is the Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 55 publications
2
38
0
4
Order By: Relevance
“…The window dressing period used was D-day-6 to D-day+ 6 (Syed & Bajwa 2018). The estimation period used 125 days (Syed & Bajwa 2018, Das, 2014. Quantitative data used were abnormal returns that occur on days around earnings announcements.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The window dressing period used was D-day-6 to D-day+ 6 (Syed & Bajwa 2018). The estimation period used 125 days (Syed & Bajwa 2018, Das, 2014. Quantitative data used were abnormal returns that occur on days around earnings announcements.…”
Section: Methodsmentioning
confidence: 99%
“…Research conducted by Fama (1970) in Syed & Bajwa (2018) regarding the efficient market hypothesis, found that capital market prices are determined by available information. This can be interpreted that every investor does not have perfect knowledge of the information; thus, it can be said that an investor is not likely to get more returns than the market.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Event studies are often carried out to examine the impact of some specific events on stock markets (Ball & Brown, 1968;Fama et al, 1969;MacKinlay, 1997;de Jong et al, 1992;Corrado, 2011). A lot of papers focus on earning announcements on market variables (Falk & Levy, 1989;Cready & Gurun, 2010;Syed & Bajwa, 2018). Other studies analyze instead the effects of dividend announcements (Lonie et al, 1996), earnings per share announcements (Foster, 1973), earnings announcements through timeliness of reporting disclosure (Chambers & Penman, 1984).…”
Section: Literature Reviewmentioning
confidence: 99%